Fresh delicious : poems from the farmer's market - Latham, Irene (Wordsong, 2016)
"In these vivid poems, blueberries are flavor-filled fireworks, cucumbers are a fleet of green submarines in a wicker sea, lettuce tastes like butter and pepper and salt, but sometimes I crunch into a leaf the very same flavor as rain. The unexpected, ingenious imagery and enticing artwork in this collection will inspire the imaginations of young readers, and show how poetry can be as fresh and delicious as the farmers market produce it celebrates."--Provided by publisher.